An analysis of the language shift in the mother tongue of the ethnic Chinese in Malaysia - Ang, Lay Hoon (2008)
Based on the statistics and data collected in a field study, this paper provides a report on the variety and amount of the mother tongue acquired by the same Chinese families over three generations, whose origins are of Fujian, Guangdong, Hakka, Chaozhou and Hainan respectively. The finding confirms that the shift in the mother tongue of the Chinese in Malaysia has already taken place, moving away slowly from the dialects of their origins and heading for English and Mandarin.